Antitumour immunity invoked by hepatic arterial infusion of first‐line oxaliplatin predicts durable colorectal cancer control after liver metastasis ablation: 8–12 years of follow‐up. Issue 7 (7th January 2020) - Abrahamsson, Hanna; Jensen, Benny V.; Berven, Lise L.; Nielsen, Dorte L.; Šaltytė Benth, Jūratė; Johansen, Jakob S.; Larsen, Finn O.; Johansen, Julia S.; Ree, Anne H.
Abstract : In colorectal cancer (CRC), hepatic arterial infusion (HAI) chemotherapy may convert primarily unresectable CRC liver metastases (CLM) into resectability, although the risk of metastatic recurrence remains high after CLM ablation. We investigated the role of antitumour immunity invoked by first‐line oxaliplatin‐HAI for long‐term CLM outcome. In a prospective study cohort of primarily unresectable CLM, we assessed patients' fms‐related tyrosine kinase 3 ligand (FLT3LG) in serum, reflecting opportune intratumoural immune activity, at baseline and following 1–3 sequences of oxaliplatin‐HAI. The end points were CLM resectability and overall survival. Patients who presented an immediate twofold increment of circulating FLT3LG during the treatment and at its completion were scored as CLM resectable (16.4% with both features), were alive at final follow‐up 8–12 years later. All patients experienced FLT3LG increase during the treatment course, but those who remained unresectable or had the disease converted but presented a slow and gradual FLT3LG accretion, later died of the metastatic disease. These data provide further support to our previous findings that tumour‐directed immunity invoked by oxaliplatin‐containing therapy predicts excellent outcome of early advanced CRC if macroscopic tumour ablation is rendered possible by the 'classic' tumour response to the cytotoxic treatment. Abstract : What's new? In colorectal cancer (CRC), hepatic arterial infusion (HAI) chemotherapy may convert primarily unresectable CRC liver metastases (CLM) into resectable CLM. The risk of metastatic recurrence remains high, however, and molecular markers for long‐term therapeutic benefit are needed. In this prospective cohort study of patients who received oxaliplatin‐HAI, the authors assessed serum FLT3LG to monitor intratumoural immune activity. All patients experienced FLT3LG increase during therapy, but only those who experienced a rapid and substantial tumour‐directed immune response were alive 8–12 years later. Monitoring the immune response via serum FLT3LG may improve the selection of CLM patients for a curative‐intent ablation procedure.